EFFECT OF PERSONAL LEARNING NETWORK INSTRUCTIONAL APPROACH ON METALWORK CRAFT PRACTICE STUDENTS’ ACHIEVEMENT IN RIVERS STATE TECHNICAL COLLEGES - Dr. Chiduhiegem C. R. WORDU; Glory N. IGWE; Baritule P. SAUE; Stanley T DIRI; Christian O. OTOBOH (European Journal of Humanities and Educational Advancements, 2023)
The study determined the effect of personal learning network instructional approach on students’ academic achievements in metalwork craft practice in technical colleges in Rivers State, Nigeria. Four (4) research Questions guided the study and Four (4) hypotheses were tested at .05 level of significance for the study. The study employed quasi-experimental research design. Specifically, non-randomized control group design involving two groups – pretest, posttest treated groups design were used for the study. The population for the study was 31 National Technical Certificate class two (NTC II) fabrication and welding craft practice students from four Technical Colleges in Rivers State for the 2020/2021 session. Out of the four Technical Colleges, two Technical Colleges were selected. The study was a census as the entire population was studied. These students in their intact classes were assigned to twenty (20) for experimental group (Personal Learning Network Instructional approach) and eleven (11) for control group (Demonstration Instructional approach). Metalwork Achievement Test were developed, validated and used for data collection. The instrument was trial tested using NTC II students from Government Technical College, Sagbama in Bayelsa State for determining its reliability. Reliability index of 0.88, 0.87, 0.89 and 0.89; were obtained for the four (4) clusters with the overall reliability of coefficient of 0.88 for Metalwork Achievement Test using Pearson Product Moment Correlation coefficient. Research Questions were answered using means and standard deviation while hypotheses were tested using Analysis of covariance (ANCOVA) at .05 level of significance. The computation was done through the help of Statistical Packages for Social Sciences Version 20 (SPSS 20). Findings of the study